2016
DOI: 10.1130/l575.1
|View full text |Cite
|
Sign up to set email alerts
|

Vertical-axis rotations accommodated along the Mid-Cycladic lineament on Paros Island in the extensional heart of the Aegean orocline (Greece)

Abstract: The Aegean-west Anatolian orocline formed due to Neogene opposite rotations of its western and eastern limbs during opening of the Aegean back-arc basin. Stretching lineations in exhumed metamorphic complexes in this basin mimic the regional vertical-axis rotation patterns and suggest that the oppositely rotating domains are sharply bounded along a Mid-Cycladic lineament, the tectonic nature of which is enigmatic. Some have proposed this lineament to be an extensional fault accommodating orogen-parallel extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 134 publications
(184 reference statements)
0
24
0
Order By: Relevance
“…Jolivet et al, 2013;Philippon et al, 2011), or normal faulting in an overall extensional regime (Gautier et al, 1999;Hinsbergen and Schmid, 2012) including vertical axis rotations in the footwall (Malandri et al, 2017). Field evi-dence is controversial, as there seems that there is neither support for a major detachment (Brun et al, 2016;Jolivet et al, 2015;Philippon et al, 2014) nor is strike-slip faulting observed on Paros, where the Mid-Cycladic Lineament might be exposed (Malandri et al, 2017;Walcott and White, 1998a). Additional complexity is added due to interaction of slab roll-back with westward migration of the Anatolian Plate since ∼ 11 Ma Ring et al, 2010).…”
Section: E-w Shorteningmentioning
confidence: 99%
See 1 more Smart Citation
“…Jolivet et al, 2013;Philippon et al, 2011), or normal faulting in an overall extensional regime (Gautier et al, 1999;Hinsbergen and Schmid, 2012) including vertical axis rotations in the footwall (Malandri et al, 2017). Field evi-dence is controversial, as there seems that there is neither support for a major detachment (Brun et al, 2016;Jolivet et al, 2015;Philippon et al, 2014) nor is strike-slip faulting observed on Paros, where the Mid-Cycladic Lineament might be exposed (Malandri et al, 2017;Walcott and White, 1998a). Additional complexity is added due to interaction of slab roll-back with westward migration of the Anatolian Plate since ∼ 11 Ma Ring et al, 2010).…”
Section: E-w Shorteningmentioning
confidence: 99%
“…Combining field data with microstructural analysis we link the different boudin generations to rheology and metamorphic conditions. Furthermore, since the amphibolites are older than the pegmatites, they record a longer deformation history and provide insights into the tectonic evolution of the Aegean, specifically the nature of east-west shortening of the domain, recognized by several authors (Urai et al, 1990;Ring and Layer, 2003;Hinsbergen and Schmid, 2012;Menant et al, 2013;Malandri et al, 2017) .…”
Section: Introductionmentioning
confidence: 99%
“…Combining field data with microstructural analysis we link the different phases of deformation to metamorphic conditions on the retrograde path. In addition to insights into the rheological and deformational evolution of the lower metamorphic levels of the Aegean metamorphic core complex, this study may help to constrain the nature of East-West shortening of the domain, recognized by several authors (Urai et al, 5 1990;Ring and Layer, 2003;Jolivet and Brun, 2010;Hinsbergen and Schmid, 2012;Menant et al, 2013;Malandri et al, 2017) .…”
Section: Introductionmentioning
confidence: 89%
“…Jolivet et al, 2013;Philippon et al, 2011), or normal faulting in an overall extensional regime (Gautier et al, Solid Earth Discuss., https://doi.org /10.5194/se-2017- Hinsbergen and Schmid, 2012) including vertical axis rotations in the footwall (Malandri et al, 2017). Field evidence is controversial, as there seems neither support for a major detachment (Brun et al, 2016;Jolivet et al, 2015;Philippon et al, 2014), nor is strike-slip faulting observed on Paros, where the Mid Cycladic Lineament might be exposed (Malandri et al, 2017;Walcott and White, 1998a). Additional complexity is added due to interaction of slab roll-back with westward migration of the Anatolian Plate since ~11 Ma (Jolivet et al, 2013;Ring et al, 2010).…”
Section: E-w Shorteningmentioning
confidence: 99%
See 1 more Smart Citation